2015
DOI: 10.14202/vetworld.2015.403-411
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common canine digestive problems compared with other health problems in teaching veterinary hospital, Faculty of Veterinary Medicine, Cairo University, Egypt

Abstract: Aim:The present study was conducted to ascertain the prevalence of common digestive problems compared to other health problems among dogs that were admitted to the teaching veterinary hospital, faculty of veterinary medicine, Cairo University, Egypt during 1 year period from January to December 2013. Also, study the effect of age, sex, breeds, and season on the distribution of digestive problems in dogs.Materials and Methods:A total of 3864 dogs included 1488 apparently healthy (included 816 males and 672 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
6
9
2
Order By: Relevance
“…The reason for this could be the preventive measures that police dogs have in our study since dermatophytosis is a contagious disease. In addition, 36 (0.3%) dogs in our study suffered from otitis, which is a rate similar to the study mentioned above in Egypt, revealing a very distinctive rate compared to the South Korean dogs’ rate (10.4%, Table-2) [7,26]. Large dogs with straight ears in our study (GSD and BM) seem to be less prone to otitis.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The reason for this could be the preventive measures that police dogs have in our study since dermatophytosis is a contagious disease. In addition, 36 (0.3%) dogs in our study suffered from otitis, which is a rate similar to the study mentioned above in Egypt, revealing a very distinctive rate compared to the South Korean dogs’ rate (10.4%, Table-2) [7,26]. Large dogs with straight ears in our study (GSD and BM) seem to be less prone to otitis.…”
Section: Discussionsupporting
confidence: 86%
“…The BM’ predisposition to cancers versus GSDs was also suggested by a study in the US conducted on GSDs and BM dogs MWDs that died in 1992 [12]. Diseases of the reproductive and urinary system each affected about 3% of dogs separately in our study (Table-3), with the Egyptian dogs having a similar rate for problems of the urinary system [26].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The present work showed that gastroenteritis had a prevalence of 13.40% of the total diseased young dogs. Contrarily, other findings had reported a prevalence of 52% in Turkey and 56.5% in Egypt [32,33]. This could be explained to a difference in geographical distribution.…”
Section: Resultsmentioning
confidence: 91%